Peran Konseling Lintas Budaya untuk Meningkatkan Toleransi di Pondok Pesantren - Hamzanwadi (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
This article is a literature study. The purpose of this article is to find out about cross-cultural counseling to increase tolerance in Islamic boarding schools. Indonesia is a country full of cultural diversity. The language, food and customs of each region have their own characteristics. This also happens in Islamic boarding schools. Each Islamic boarding school environment also has its own characteristics. Each student who comes from a different region brings their own regional culture. This gives rise to social conflict between one another. Tolerance is an important value that displays itself as an individual attitude and contributes to peace and order. Tolerance can prevent conflict in groups. Islamic boarding school-based schools have a role in developing the character of tolerance in students. A counselor needs to have the ability to be sensitive to cultural differences. There is a need to understand the cultural diversity that exists in Islamic boarding school-based schools. By understanding cultural differences, counselors can understand cultural biases that occur between one student and another. Cultural biases that cause conflict in Islamic boarding school-based schools can also be minimized and can be an alternative for conflict prevention. Cross-cultural counseling has the function of trying to understand humans as a whole in their cultural context through an interpretive approach. The psychological function of culture allows a study to understand a person's behavior through the expected social roles, norms and regulations that apply in their environment. The existence of two-way communication in cross-cultural counseling provides students with an understanding of the values ​​and norms contained in each culture. With cross-cultural counseling, it is hoped that it will be able to minimize cultural bias and create tolerance in Islamic boarding school-based schools.